The Strength of Traditional Villages in Managing Coastal Areas in Bali - I Made Arjaya (Law Doctoral Community Service Journal, 2022)
The existence of Traditional Villages in Bali is still alive and active, supported by Hindu religious culture which is very thick in the daily life of the people who support the Traditional Village. The island of Bali is an island that has a very charming coastline that surrounds it. From the beach in the west of the island of Bali, namely in Jembrana Regency, there are Gilimanuk Beach, Melaya Beach, Candikusuma Beach, Pefruit Beach, Baluk Rening Beach, Pengambengan Beach, Perancak Beach, Tumbles Beach, Yeh Embang Beach, Rambut Siwi Beach, Pulukan Beach, Pekutatan Beach, Selabih Beach. In Tabanan Regency there are Soka Beach, Antap Beach, Bebali Beach, Kelecung Beach, Tidal Beach, Batu Tampih Beach, Belong Beach, Kutikan Beach, Tanah Lot Beach. In Badung Regency there are Nyanyi Beach, Cemagi Beach, Munggu Beach, Seseh Beach, Canggu Beach, Batu Bolong Beach, Berawa Beach, Kayu Putih Beach, Batu Belig Beach, Petitenget Beach, Seminyak Beach, Legian Beach, Kuta Beach, Segara Beach, Beach Germany, Tuban Beach, Kelan Beach, Kedonganan Beach, Jimbaran Beach, Uluwatu Beach, Nyang Nyang Beach, Pandawa Beach, Tanjung Benoa Beach. In Denpasar City there are Benoa Beach, Serangan Beach, and Sanur Beach. In Gianyar there is Purnama Beach, Saba Beach, More Beach. In Klungkung Regency there is Watu Klotok Beach. In Karangasem Regency there are Padangbai Beach, Candidasa Beach, Tulamben Beach. In Buleleng Regency there is Lovina Beach, and other beaches.